2000
DOI: 10.1094/cchem.2000.77.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature, Sonication Time, and Power Settings on Size Distribution and Extractability of Total Wheat Flour Proteins as Determined by Size‐Exclusion High‐Performance Liquid Chromatography

Abstract: Cereal Chem. 77(5):685-691The size-exclusion (SE) HPLC profile of total protein extract obtained by sonication of flour samples at ambient temperature showed marked instability on reinjection. Instability was related to the presence of flour proteases that were inactivated by thermal treatment of flour samples at 60°C. Extraction of flour protein by sonication was a function of ultrasonic energy (sonication time × power product) delivered to flour sample. As protein solubility increased, the proportions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(176 citation statements)
references
References 7 publications
9
166
0
1
Order By: Relevance
“…Protein fractions were determined by size exclusion (SE) HPLC. For this purpose, the method of Morel et al (2000) was slightly modified and a phosphate buffer was used to extract SDS-soluble proteins. Five fractions of SDS-soluble proteins (F1-F5) were separated (Dachkevitch and Autran 1989).…”
Section: Wheat Baking Quality Parametersmentioning
confidence: 99%
“…Protein fractions were determined by size exclusion (SE) HPLC. For this purpose, the method of Morel et al (2000) was slightly modified and a phosphate buffer was used to extract SDS-soluble proteins. Five fractions of SDS-soluble proteins (F1-F5) were separated (Dachkevitch and Autran 1989).…”
Section: Wheat Baking Quality Parametersmentioning
confidence: 99%
“…The SE-HPLC apparatus (Waters model LC Module1 plus) was equipped with an analytical column TSK G4000-SW (Merck, France; 7.5×300 mm) and a guard column TSK G3000-SW (Merck, France) (7.5× 75 mm), as previously described. 18 Once corrected for their different solid-to-solvent ratios during extractions, areas (in arbitrary units) of SDS-soluble and DTE-soluble proteins were added, and the sum (i.e. total extractable proteins) was expressed as percents of the corresponding total area calculated for semolina (for durum wheat pasta) or a blend of 65% semolina and 35% legume flour (for legume pasta; on equivalent dry protein basis).…”
Section: Protein Size Distribution Measurementmentioning
confidence: 99%
“…In durum wheat semolina, fractions S1 (6%) and S2 (19%) could be assimilated to polymeric glutenin proteins, fractions S3 (7%) and S4 (34%) could be assimilated to gliadins and fraction S5 (14%) corresponded to watersoluble proteins (albumins and globulins) 18 (Figure 8b). Split pea and faba bean proteins were mainly composed of proteins with a molecular weight inferior to 100 kDa.…”
Section: Characterisation Of Durum Wheat Semolina and Durummentioning
confidence: 99%
“…Cloud retention after sonication may be attributed to dispersion stability of macromolecules due to the promotion of certain chemical reactions during sonication (Floros & Liang, 1994;Mason, 1998;McClements, 1995). High-intensity ultrasound enhances protein solubility (Krešić, Lelas, Jambrak, Herceg, & Brnčić, 2008) by changing protein conformation and structure in such a way that hydrophilic parts of amino acids from inside are opened toward water (Morel, Dehlon, Autran, Leygue, & Bar-L'Helgouac'h, 2000;Moulton & Wang, 1982). Lacroix, Fliss, and Makhlouf (2005) reported that electrostatic interactions between PME and its substrate pectin have a major impact on orange juice cloud stability.…”
Section: Mechanism Of Cloud Retention During Sonicationmentioning
confidence: 99%